WORK AGREEMENT BETWEEN MEDAN HAJI HOSPITAL AND TENDER WINNING CONTRACTORS (According To The Regulation Of The Governor Of North Sumatera No 52 Of 2015 Concerning Procurement Of Goods And Services Of Regional Public Services In Medan Haji Hospitals, North - Revi Fauzi Putra Mina (NOMOI Law Review, 2021)
Procurement of Goods and Services is expected to be carried out effectively and efficiently with the principles of fair competition, transparency, openness, and fair treatment for all parties, according to Presidential Regulation No. 54 of 2010 concerning Procurement of Government Goods and Services is an activity to obtain goods and services by the Ministry / Institutions / Work Units of Regional / Institutional Devices and Regulations of North Sumatra Governor No 52 of 2015 concerning Procurement of Goods and Services for Regional Public Service Agencies at other Medan Hajj Hospital in North Sumatra Province, the process of which starts from needs planning to all activities to obtain goods and services. The method used is a research method with a statutory approach and acase approach. The results of this study explain first, that the implementation of the agreement carried out by field hajj hospital with the tender winner in the contract of procurement of goods and services carried out by the Hajj field hospital as stipulated in the North Sumatra Governor Regulation No. 52 of 2015 concerning Procurement of Public Service Goods and Services Region at Medan Haji Hospital North Sumatra Province As a responsibility when the default service provider means that it must be responsible for the service provider. Keywords: Implementation, Procurement, Legal Responsibilities.